2021
DOI: 10.1002/ajmg.a.62472
|View full text |Cite
|
Sign up to set email alerts
|

The burden of pathogenic variants in clinically actionable genes in a founder population

Abstract: Founder populations may be enriched with certain genetic variants of high clinical impact compared to nonfounder populations due to bottleneck events and genetic drift. Using exome sequencing (ES), we quantified the load of pathogenic variants that may be clinically actionable in 6136 apparently healthy adults living in the Lancaster, PA Old Order Amish settlement. We focused on variants in 78 genes deemed clinically actionable by the American College of Medical Genetics and Genomics (ACMG) or Geisinger's MyCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The observed yield of SFs, 2.7% (7/261), corresponds to an expected rate of < 3% of individuals who are commonly identified as carriers of at least one reportable SF in one of those genes defined by the ACMG. The proportion of SFs in ES/GS may vary depending on the occurrence of specific variants in founder populations [ 33 ]. Referring the SF variants to clinicians is crucial to provide an early intervention and to reduce the life-threatening effects.…”
Section: Discussionmentioning
confidence: 99%
“…The observed yield of SFs, 2.7% (7/261), corresponds to an expected rate of < 3% of individuals who are commonly identified as carriers of at least one reportable SF in one of those genes defined by the ACMG. The proportion of SFs in ES/GS may vary depending on the occurrence of specific variants in founder populations [ 33 ]. Referring the SF variants to clinicians is crucial to provide an early intervention and to reduce the life-threatening effects.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of PVs in the isolated populations reported herein are in line with previous reports [ 12 , 13 ]. Specifically, Khayat et al [ 13 ] reported 48 PVs in the AR genes (24 novel PVs) in an isolated community of Muslim Arabs in Israel ( n = 50) based on the results of WES in that population [ 14 ]. The Israeli population genetic carrier screening program is included in the health basket and hence is covered by the health maintenance organizations (HMOs) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rare variants that are common in at least one population should be thoroughly evaluated for pathogenicity. While there are documented examples of disease alleles with elevated allele frequencies in population-specific founder variants, [68][69][70][71] detailed phenotypic and functional characterization of variants is critical for variant curation efforts.…”
Section: Interpretation Of Rare Variants For Clinical Diagnosticsmentioning
confidence: 99%